Money Politics Phenomenon in The Village Head Election of Jemanten District, East Lampung Regency, 2023 - Juwita Zahara (Jurnal Terekam Jejak, 2024)
The Head Village Election has arisen as a major source of concern in society, particularly among rural areas. Bribery to secure votes is not uncommon in this setting, as some consider Head of Village elections to be less important. Candidates for Head of Village positions offer money to the community as part of their election campaign, focusing on people who might otherwise not vote. The purpose of this study is to look into the reasons why people accept money from Head of Village candidates. Using a qualitative approach and a Normative Juridical framework, the study focuses on Negeri Jemanten Village people who first refused to participate in the election owing to bribery. The research is based on Alfred Schutz's phenomenological theoretical standpoint. The data suggest that people's propensity to visit polling booths can be impacted by financial incentives, resulting from a lack of understanding about the Head of Village candidates.